A revision of the genus Leptogorgia Milne Edwards & Haime, 1857 (Coelenterata: Octocorallia: Gorgoniidae) in the eastern Pacific - Breedy, Odalisca; Guzman, Hector M. (Zootaxa, 2007)
The species of the widespread gorgoniid genus Leptogorgia, which occur along the eastern Pacific, are taxonomically revised based on original type material of all species described until now and reference specimens from recent surveys and expeditions along the Pacific coast of Panama, and Costa Rica. As a result, 21 species are recognized as valid and one as dubious. Lectotypes are assigned for eight species in order to establish their taxonomic status. All the species are described and illustrated. The fauna herein reported does not represent overall diversity or geographical range of each species but adds new reports. The present count is 16 species for Panama, 11 for Costa Rica, 7 for Mexico, 6 for El Salvador, 4 for Peru, 4 for Ecuador, 3 for Colombia, 2 for California, 2 for Nicaragua, and 2 for Chile.